CT and MR imaging patterns for pancreatic carcinoma invading the extrapancreatic neural plexus (Part I): Anatomy, imaging of the extrapancreatic nerve - Zuo, Hou-Dong (Baishideng Publishing Group Co., Limited, 2012)
Pancreatic carcinoma is an extremely high-grade malignant tumor with fast development and high mortality. The incidence of pancreatic carcinoma continues to increase. Peripancreatic invasion and metastasis are the main characteristics and important prognostic factors in pancreatic carcinoma, especially invasion into the nervous system; pancreatic nerve innervation includes the intrapancreatic and extrapancreatic nerves. A strong grasp of pancreatic nerve innervation may contribute to our understanding of pancreatic pain modalities and the metastatic routes for pancreatic carcinomas. Computed tomography (CT) and magnetic resonance imaging (MRI) are helpful techniques for depicting the anatomy of extrapancreatic nerve innervation. The purpose of the present work is to show and describe the anatomy of the extrapancreatic neural plexus and to elucidate its characteristics using CT and MRI, drawing on our own previous work and the research findings of others.